World religions - "Coogan, Michael D. (ed.)" (London, 2003)
A fabulous collaboration of images and text encompassing all facets of our world's religions. A fabulously illustrated and dependable guide for amateurs and experts alike, World Religions is a must have for every reference book shelf. Covering all the complex issues, this is a thoroughly accessible text and reflects all the ideas of the moment - this book is designed as an illuminating introduction to the world's living faiths. This book focuses on all of the main religions around the world proving a detailed and comprehensive insight into the life they evoke. We are given the opinions of the experts as each chapter is written by an acknowledged authority in the appropriate field. Michael D. Coogan provides a thorough introduction providing the perfect backdrop for what is to follow. Coogan furnishes us with an all-round vision, discussing such topics as: the definition of religion; the spectrum of academic approaches; ancient religions and those of pre-literate cultures; the relationship throughout history between religion and politics; and the ways in which religions have our cultures and our everyday lives.
Keywords: Religion